The Translation of Nature Terminology in Literary Texts: A Case Study - Sinu Raluca (Lublin Studies in Modern Languages and Literature, 2024)
This paper investigates the way nature-related terms are rendered in literary texts, highlighting possible explanations for the translation decisions. The discussion will be illustrated with examples of terms related to wetland and to the vegetation specific for this area, extracted from the novel Where the crawdads sing (2018) by Delia Owens and its Romanian translation. The conclusions show that there are several reasons why the translator may opt for a less accurate rendering of nature terminology, including the translator’s perception of the aim of the target text, e.g. entertainment rather than information, or the translator’s (limited) knowledge of the field.
Keywords: nature terminology; literary text; equivalence; wetland; vegetation